The relationship between geochemical background values of MgO and SiO₂ and regional population longevity: evidence from Yunnan, China - Zhou, Xin; Wang, Jiaxue; Zhu, Shuangshuang; Lai, Min (Frontiers in Public Health, 2025)
IntroductionThe relationship between geographical environments and human health has been a long-standing focus of scientific inquiry. Magnesium (Mg) and silicon (Si), as essential elements for the human body, play vital roles in individual health and may influence longevity. However, the extent to which the statistical characteristics of population longevity are associated with geochemical background values at a regional scale remains an important question.MethodsThis study examines Yunnan, China, a region with diverse and complex geographical conditions, and used global autocorrelation analysis, cluster and outlier analysis, and hotspot analysis to comprehensively analyze the Spatial Distribution Characteristics of magnesium oxide (MgO) and silicon dioxide (SiO₂) background values. It further investigates the individual and synergistic relationships of these geochemical factors with population longevity at the county scale in Yunnan using the Spearman rank correlation.ResultsThe results demonstrate that the MgO background value (ω(MgO)) exhibits a significant positive correlation with the Ultra-octogenarian Index and has a positive synergistic effect on regional longevity levels. In contrast, the SiO₂ background value (ω(SiO₂)) shows a significant negative correlation with both the longevity index and the Ultra-octogenarian Index, while the ratio of Si to Mg (ω(Si/Mg)) is also significantly negatively correlated with the Ultra-octogenarian Index.DiscussionThese findings suggest that MgO-enriched natural environments may positively contribute to regional population longevity, while excessively high SiO₂ background values may have a detrimental effect. This study offers a novel perspective on the relationship between regional longevity levels and natural geographical environments, which may inform the selection and sustainable development of longevity-oriented tourism destinations.